2018
DOI: 10.1103/physrevfluids.3.073901
|View full text |Cite
|
Sign up to set email alerts
|

Resolvent analysis of separated and attached flows around an airfoil at transitional Reynolds number

Abstract: We analyze the resolvent operator in three flows around a nominal NACA-0012 airfoil at Re C = 50, 000 and 5 o angle of attack. In particular, we study two naturally developing flows (around the airfoil with straight and blunt trailing edges) and one tripped flow. The naturally developing flows exhibit laminar separation, transition and turbulent reattachment, while the tripped flow remains attached in the suction side. For all cases, the time-averaged flow fields are computed from separate DNS simulations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The mode shapes for intermediate frequencies have a mix of both linear mechanisms as seen for ω = 12 in figure 16. These results are consistent with Thomareis & Papadakis (2018) and Yeh & Taira (2019), who computed resolvent modes for a NACA 0012 airfoil at similar Reynolds numbers and angles of attack from time-averaged DNS and large-eddy simulation (LES) data, respectively. The latter study also identified two branches in the eigenspectrum of the LNS operator which were grouped into wake or shear layer modes.…”
Section: A10 Case: Multiple Linear Mechanismssupporting
confidence: 87%
See 1 more Smart Citation
“…The mode shapes for intermediate frequencies have a mix of both linear mechanisms as seen for ω = 12 in figure 16. These results are consistent with Thomareis & Papadakis (2018) and Yeh & Taira (2019), who computed resolvent modes for a NACA 0012 airfoil at similar Reynolds numbers and angles of attack from time-averaged DNS and large-eddy simulation (LES) data, respectively. The latter study also identified two branches in the eigenspectrum of the LNS operator which were grouped into wake or shear layer modes.…”
Section: A10 Case: Multiple Linear Mechanismssupporting
confidence: 87%
“…For low Reynolds number bluff body wakes, this could be as few as a single point (see Gómez et al 2016b;Symon et al 2019). In a similar vein, Beneddine et al (2016) and Thomareis & Papadakis (2018) have been able to estimate the spectra at various points of the flow using only the aforementioned measurements. The success of the method relies on the low-rank nature of the (linear) resolvent operator, which one obtains after linearising the Navier-Stokes equations around the (turbulent) mean flow, and treating the nonlinear terms as a source of intrinsic forcing (McKeon & Sharma 2010).…”
Section: Introductionmentioning
confidence: 94%
“…The resolvent operator is derived from the Navier-Stokes equations linearized about the turbulent mean flow and constitutes a transfer function in the frequency domain between terms that are nonlinear and linear with respect to fluctuations to the mean. Resolvent analysis has proven to be a useful tool for understanding and modelling a wide range of flows, including wall-bounded flows (Sharma & McKeon 2013;Morra et al 2019), free-shear flows (Jeun, Nichols & Jovanović 2016;Schmidt et al 2018) and aerodynamic wakes (Thomareis & Papadakis 2018;Symon, Sipp & McKeon 2019;Yeh & Taira 2019). Whereas Beneddine et al (2016) constructed their model using only the first singular mode of the resolvent operator (obtained via singular value decomposition), our model relaxes this a priori assumption and allows the known data to self-select the relevant portion of the resolvent operator.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis is performed in frequency space, relies on a mean flow as input, and is specific to a given frequency. It has been used to study the flow over airfoils [11,13,10], however mainly for control purposes and accurate pressure predictions were not provided. In fact, Symon et al [10] remarked that it would be great to see a resolvent pressure prediction for an airfoil.…”
Section: Introductionmentioning
confidence: 99%